L’identité dans The Talos Principle, The Stanley Parable et The Swapper - Tristan Bera (Conserveries Mémorielles)
In their paper Au-delà de l'identité, Roger Brubaker and Frédéric Junqua explain that « identity is something everybody has, or would have, or are searching for » (Brubaker, Junqua, 2001, p. 74). This questioning around the concept of identity has multiple aspects in our everyday live, through politic, physical aparence, historical context etc... Identity is everywhere. However, this concept, because of its polysemy, seems to be incertain, indefined. The formation of personnal identity attracts the same questions : is it an innate quality, essence of the individual expressing through time ? Is it acquired, influenced, always building up like the constructivism enunciate it ? Is it something else ? Through the games Talos Principle (Croteam, Devolver digital, december 2014), The Stanley Parable (Galatic cafe, october 2013) et The Swapper (Facepalm Games, may 2013), this study asks character/avatar's identity linked to their environment and themselves to make the idea of reciprocal grants emerges in identity development.